Psychic status in a woman with climacteric syndrome and cardiac complaints - Ekaterina N. Beliaeva; Iana V. Kostroma; Liubov V. Kuznetsova; Elena L. Khazova; Irina E. Zazerskaia (IP Berlin A.V., 2021)
Aim. To assess the features of psychoemotional status in women with climacteric syndrome, manifested by cardiac symptoms. Materials and methods. The study included 28 women aged 44 to 56 years (M=53,80,7) with menopause-associated complaints, manifested mainly by cardiac symptoms. Modified Kupperman-Uvarova menopausal index was used to diagnose climacteric syndrome and assess its severity. To study the psychoemotional status the Tsung anxiety and depression self-assessment scales were used. Holter ECG monitoring and echocardiography were performed on the ASTEL LTD Cardio DM-3 apparatus for 72 hours. Results. The most common cardiac complaints in menopausal syndrome were: increased blood pressure, palpitations, recurrent chest pain. Ventricular premature beats were the most common finding. Emotional-affective disorders were found in women of the study group. For women with a mild climacteric syndrome, signs of mood instability, increased emotional lability, irritability, and low levels of anxiety are characteristic. Women with moderate climacteric syndrome complained of anxiety, irritability, anger, and prolonged episodes of decreased mood. According to the anxiety and depression self-assessment scales, these women typically had emotional-affective disorders which manifested by high levels of anxiety, and 29% of them had mild levels of depression. Women with severe climacteric syndrome complained of prolonged episodes of decreased mood, sleep disturbances, and performance impairment; these women predominantly had high levels of anxiety and moderate levels of depressive disorder. Conclusion. In women with climacteric syndrome, major symptoms are neurovegetative, with a predominance of complaints associated with ventricular rhythm disorders. For climacteric syndrome, affective spectrum disorders are characteristic. The more pronounced the climacteric syndrome, the more severe the anxiety-depressive disorder.